Maternal Infectious Diseases, Antimicrobial Therapy or Immunizations: Very few Contraindications to Breastfeeding - Noni E Macdonald (Canadian Journal of Infectious Diseases and Medical Microbiology)
The Canadian Paediatric Society recommends exclusive breastfeeding as the optimal method of infant feeding for the first six months of life for healthy, term infants (1). There are many benefits associated with breastfeeding, including nutritional, immunological, psychological, developmental, environmental, social, economic and health (eg, decrease in infectious diseases) (2-4). To promote, protect and support breastfeeding, every effort must be made to minimize contraindications to breastfeeding, particularly unnecessary ones. The present article summarizes the maternal infectious diseases in which continuing breastfeeding is recommended, the very few infectious diseases in which it is not recommended, the rare instances in which maternal antimicrobial therapy indicates a caution for breastfeeding, and the continuation of breastfeeding when a mother or her infant is receiving a routine recommended immunization.